2015
DOI: 10.1108/ijilt-05-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural comparison of concepts in computer science education

Abstract: Purpose -The development of a K-12 computer science curriculum based on constructivist principles needs to be informed by knowledge of content and process concepts that are central to the discipline of computer science. The paper aims to discuss this issue. Design/methodology/approach -Taking a cross-cultural approach and using an experimental design (a SPF-2•15×16 split-plot design), this study compares the combinations of content and process concepts identified as important in Germany with those considered r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Erdamar and Alpan [7] recognised the epistemological beliefs and problem solving skills changed during the process of teaching practice. A cross-cultural study of concepts in CS education by Zendler et al [8] comparing professorial analysis of two nations' CS curriculum indicated that although different in focus, i.e. one being more technical compared to the other being more soft-skill focus, both were analysed to be comparable.…”
Section: Literaturementioning
confidence: 99%
“…Erdamar and Alpan [7] recognised the epistemological beliefs and problem solving skills changed during the process of teaching practice. A cross-cultural study of concepts in CS education by Zendler et al [8] comparing professorial analysis of two nations' CS curriculum indicated that although different in focus, i.e. one being more technical compared to the other being more soft-skill focus, both were analysed to be comparable.…”
Section: Literaturementioning
confidence: 99%